The Relationship Between the Serum Resistin Levels of Patients with COPD Attack and Airway Obstruction - Yildirim, Funda; Turgut, Teyfik; Kirkil, Gamze; Ustundag, Bilal (Aves, 2013)
Aim: Malnutrition occurs in approximately one-third of patients with chronic obstructive pulmonary disease (COPD), and this situation may further worsen in advanced stages of the disease. It is known that an increased systemic inflammatory response is related to weight loss. We aimed to evaluate the levels of plasma resistin, leptin and inflammatory cytokines in patients with acute exacerbations of COPD, and to investigate the relationship between the degree of airway obstruction in this study. Materials and Methods: Thirty-eight COPD attack patients who were hospitalised to our clinic and 21 healthy individuals as a control group enrolled into the study. Demographic data, smoking history, disease duration and previous medication were recorded. Serum cytokine, leptin, and resistin levels were evaluated in the COPD and healthy control groups. In the COPD group, venous blood samples were taken again on the 15th day, and pulmonary function tests were performed. Results: The median age of the COPD group (M/F=20/18) was 61.50 +/- 9.03 years, and 56.52 +/- 9.90 years in the control group (M/F=12/9). There was no significant difference in sex and age between the groups. Serum TNF-alpha, IL-1 beta, IL-6, IL-8, leptin and resistin levels were significantly higher in the COPD group than in the control group. Serum TNF-alpha, IL-1 beta, IL-6, IL-8, leptin, resistin levels in COPD patients on the 15th day were significantly lower than the levels on the first day (p< 0.001 for all parameters). FEV 1 and FVC parameters were increased on the 15th day when compared with the first day (p< 0.001 for FEV 1, p< 0.05 for FVC). No change was observed in FEV 1 /FVC (p> 0.05). Only FEV 1 and TNF-alpha levels were mildly correlated on the first day of the study (p< 0.05, r=0.364). A similar correlation was observed on the 15th day of the study (p< 0.05, r=0.447). Conclusion: Because the levels of serum leptin and resistin increase during COPD attack and decrease to normal levels after attack therapy, both can be used as an inflammatory marker.
Keywords: COPD; attack; leptin; resistin; proinflammatory cytokine